Red-lined circle : an essay and short stories - Abraham, Rajadurai (2009)
The project that I have undertaken is one that allows me to reveal my four years of study through the process of not just writing an academic piece but to apply what I have read in my years here creatively. As such I attempt to construct pieces of fiction through academia into revealing an essence of the real. Fictional writings in general have come about through various sources, some happen through observing others in their daily lives, some through research, and others perhaps are influenced through various forms of media. For me personally, I was influenced heavily by music and readings of the above stated novels. Mostly, books that I happen to find interesting characters that seem to grow on me, and help me find a voice perhaps for the protagonists that are developed within my own texts. The essay that explains it all, essentially reveals the working of my mind through the whole process.